The global cryosphere past, present, and future - Barry, Roger Graham (Cambridge University Press, 2011)
"This is the first textbook to address all the components of the Earth's cryosphere - all forms of snow and ice, both terrestrial and marine. It provides a concise but comprehensive summary of snow cover, glaciers, ice sheets, lake and river ice, permafrost, sea ice and icebergs - their past history and projected future state. It is designed for courses at upper undergraduate and graduate level in environmental science, geography, geology, glaciology, hydrology, water resource engineering and ocean sciences. It also provides a superb up-to-date summary for researchers of the cryosphere. The book includes an extensive bibliography, numerous figures and color plates, thematic boxes on selected topics and a glossary. The book builds on courses taught by the authors for many decades at the University of Colorado and the University of Alberta. Whilst there are many existing texts on individual components of the cryosphere, no other textbook covers the whole cryosphere"--